Єпископ Веніамін (Сахновський): духовно-релігійна та культурно-просвітницька діяльність - Кагамлик, С. (Український історичний журнал, 2020)
Метою статті є аналіз життя й діяльності єпископа Веніаміна (Сахновського), виявлення специфіки його архіпастирського служіння на теренах Коломенської, В’ятської, Воронезької єпархій, реконструкція кола оточення та спілкування. Новизна дослідження. Уперше в українській історичній науці розглянуто постать архієрея, обґрунтовано його українське походження та специфіку архіпастирської діяльності згідно з українськими традиціями. Методологія базується на поєднанні методів і принципів історизму, системності, культурно-історичної типології. За допомогою історично-антропологічного методу з’ясовано ієрархію духовних цінностей та змодельовано соціальний портрет єпископа. Висновки. Життєві віхи, духовно-релігійна, культурно-просвітницька діяльність та коло спілкування ієрарха підтверджують його українське походження й духовне служіння згідно з національними традиціями. Архієрей підтримував тісні контакти з вихованцями Києво-Могилянської академії – київським архієпископом Рафаїлом (Заборовським), чернігівським єпископом Амвросієм (Дубневичем), ростовським митрополитом Арсенієм (Мацієвичем) та ін. Архіпастирська діяльність його на теренах різних російських єпархій засвідчує, що він продовжував просвітницькі заходи своїх попередників і сучасників – архієреїв-українців, у започаткуванні й розвитку шкіл-семінарій, забезпеченні їх викликаними з Києва та Чернігова учительськими кадрами. У сфері місійної діяльності єпископ Веніамін не обмежувався звичним для того часу виконанням указів Синоду, а виявляв ініціативу щодо християнізації удмуртів, матеріального забезпечення місії, у тому числі власними коштами, захисту від утисків татар і місцевих властей. The purpose of this article is established as a complex analysis of life and activity of bishop archiereus Veniamin (Sakhnovskyi), determination of specifics of his archpastoral ministry on the terrenes of Kolomna, Vyatka, and Voronezh eparchies, reconstruction of circle of environment and communication. A novelty of research – it has been reiewed the figure of archiereus Veniamin in the Ukrainian historical studies for the first time, it has been reasoned his Ukrainian origin and specifics of archpastoral activity in accordance with the Ukrainian traditions. The research methodology is based on a combination of methods and principles of historicism, systematization, cultural and historical typology. The hierarchy of spiritual values was clarified with the help of the historical-anthropological method and the social portrait of Bishop Veniamin was modeled. Conclusions. The life milestones, religious and cultural-educational activity, circle of communication of Veniamin confirm his belonging to the Ukrainian Orthodox community and service according to the Ukrainian traditions. Archiereus kept in close touch with Kyiv-Mohyla Academy students – archbishop of Kyiv Rafail (Zaborovskyi), bishop of Chernihiv Amvrosii (Dubnevych), metropolitan of Rostov Arsenii (Matsiievych) and others, as it brightly appears from last will and testament of the preconsecrated. An archpastoral activity of Sakhnovskyi on the terrenes of various Russian eparchies gives evidence of that he has continued education activities of his predecessors and cotemporaries archiereuses-Ukrainians – in the beginning and development of schools-seminaries, their provision with the called from Kyiv and Chernihiv scholastic staff. In the field of mission activity, the bishop Veniamin was not limited to customary for that time decrees of the Synod, and showed his own initiative regarding activities for spread of Christianization among the Udmurts, material support of the mission, including support with his personal finances, protection new converts from infringement of the Tatars and local authorities.